PENDAPATAN DIVERSIFIKASI USAHATANI PADI DAN TERNAK ITIK PEDAGING SERTA FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI ITIK PEDAGING DI KABUPATEN PRINGSEWU - Dwi Novitasari; Sudarma Widjaya; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to analyze income of rice farming and duck diversification, contribution of income from duck farming to farmers’ household, and identify the factors that influence the production of duck livestock. The research was conducted in Pringsewu District in January - February 2018. The sample was selected using a snowball sampling method and consisted of farmers who cultivated rice farming and ducks. The data were analyzed using farm income analysis and Cobb Douglas analysis. The results showed that income of farmers from farming diversification of rice and duck was profitable. Contribution of income from duck farming to farmers’ household income was higher than that from other sources. Three factors influencing duck production were bran feed, concentrate feed, and mortality rate.Key words : diversification, duck livestock, farm income, rice farming